CEFR AND UZBEK STANDARD, NATIONAL AND INTERNATIONAL LANGUAGE REQUIREMENTS (Ustozlar uchun, 2025)
This article explores the relationship between the Common European Framework of Reference for Languages (CEFR) and Uzbekistan’s national language policy. It examines how CEFR has been implemented in Uzbek foreign language education and how it aligns with or differs from the country’s national and legal language requirements. The study emphasizes the balance between international language standards and the protection of the Uzbek language as the state language. It also discusses current reforms, challenges, and recommendations for harmonizing national and international standards.